2009
DOI: 10.1111/j.1365-277x.2008.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of nut consumption on plasma total polyphenols, antioxidant capacity and lipid peroxidation

Abstract: Consumption of both nuts increased plasma polyphenol concentrations, increased the total antioxidant capacity and reduced plasma lipid peroxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 46 publications
8
71
1
6
Order By: Relevance
“…On the other hand, we observed that the TMD þ Nuts group presented higher plasma TAC compared to control group levels as reported in previous studies (Torabian et al, 2009). However, the supplementation with nuts is not equally effective to increase antioxidant capacity as compared to VOO.…”
Section: Discussionsupporting
confidence: 47%
“…On the other hand, we observed that the TMD þ Nuts group presented higher plasma TAC compared to control group levels as reported in previous studies (Torabian et al, 2009). However, the supplementation with nuts is not equally effective to increase antioxidant capacity as compared to VOO.…”
Section: Discussionsupporting
confidence: 47%
“…Four recent studies have assessed the acute effects of meals enriched with nuts on postprandial oxidation in comparison with nut-free meals [99,103,104,105]. Results have again been mixed, as two studies using walnuts [103] and almonds [104] had no discernible effect on oxidation biomarkers, while one study with almonds [99] and another study examining both almond and walnut meals [105] showed beneficial effects on postprandial oxidative stress.…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fmentioning
confidence: 99%
“…Results have again been mixed, as two studies using walnuts [103] and almonds [104] had no discernible effect on oxidation biomarkers, while one study with almonds [99] and another study examining both almond and walnut meals [105] showed beneficial effects on postprandial oxidative stress.…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fmentioning
confidence: 99%
“…However, when the rooibos extract and RPO were fed together, the combination resulted in a significant increase in plasma total polyphenol and plasma TAC measured only as TEAC. Some studies in humans have shown that the plasma total polyphenol content parallels the plasma TAC after the intake of polyphenol-rich diets (Henning et al, 2004;Torabian et al, 2009;Wang et al, 2012), suggesting that phenolic compounds are the major contributors to the plasma TAC, a fact that we also suspected may be true in animals. The TEAC assay is based on the inhibition of the absorbance of the ABTS radical cation (ABTS •+ ) by antioxidants.…”
Section: Discussionmentioning
confidence: 90%